Fischer–Tropsch synthesis over Pd promoted cobalt based mesoporous supported catalyst - Gupta Pavan Kumar; Mahato Abhishek; Gupta Goutam Kishore; Sahu Gajanan; Maity Sudip (Oil & Gas Science and Technology, 2021)
The present study focuses on the catalytic conversion of syngas (CO + H2) through Fischer–Tropsch (FT) route using two identically prepared 0.1 wt.% palladium promoted Mesoporous Alumina (MA) and SBA–15 supported Co (15 wt.%) catalysts. The Fischer–Tropsch activity is performed in a fixed bed tubular reactor at temperature 220 °C and pressure 30 bar with H2/CO ratio ~2 having Gas Hourly Space Velocity (GHSV) of 500 h−1. Detail characterizations of the catalysts are carried out using different analytical techniques like N2 adsorption-desorption, Temperature-programmed reduction with hydrogen (H2-TPR), Temperature-programmed desorption with NH3 (NH3-TPD), X-Ray Diffraction (XRD), and Transmission Electron Microscopy (TEM). The results show that the SBA–15 supported catalyst exhibits higher C6–C12 selectivity (57.5%), and MA supported catalyst facilitates the formation of higher hydrocarbons (C13–C20) having a selectivity of 46.7%. This study attributes the use of both the support materials for the production of liquid hydrocarbons through FT synthesis.